PANEL METHOD CACULATIONS OF WING - TAIL INTERFERENCE EFFECTS (Journal of Engineering, 2009)
A low-order panel method was used to predict the flow characteristics between two sets of wings representing wing and tail. Constant source and doublet singularities with Drichlet boundary condition are used on the body surfaces. Distance and setting angle changes of the tail are studied to predict the air flow characteristics. Since the flow is incompressible non-viscous (potential flow), the results obtained contain a large physical evidence and may give a good design tool for aircraft stability consideration. A FORTRAN program was built to calculate the flow characteristics and then validated with published data. Highly acceptable results are obtained as compared with these data, so that; the program can be used for discussing the design or control parameters of such aerodynamical problems